2002
DOI: 10.1111/j.1651-2227.2002.tb02881.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blood transfusions on cerebral haemodynamics in preterm infants

Abstract: Aim: To assess the possible cerebral haemodynamic changes occurring in preterm infants after blood transfusions. Methods: Preterm infants who had undergone blood transfusions were prospectively studied using both near infrared spectroscopy and cerebral Doppler ultrasonography. Results: Fourteen infants (mean gestational age 29.6 wk, SD 2.6; mean birthweight 1430 g, SD 332) were studied at the mean age of 29 (SD 14) d. A significant increase in oxygenated haemoglobin (O2Hb), deoxygenated haemoglobin (HHb), mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 15 publications
5
27
0
1
Order By: Relevance
“…In addition, to better interpret our findings, we studied tissue perfusion by Doppler ultrasound. As expected, and in agreement with previous articles, 8,9 we found that blood transfusions were followed by an increase in cerebral oxygenation (rSO2C). However, we observed that this increase in oxygen delivery was compensated by a decrease in oxygen blood extraction (FOEC): we speculated that this occurs to keep the oxygen consumption of cerebral tissue constant.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, to better interpret our findings, we studied tissue perfusion by Doppler ultrasound. As expected, and in agreement with previous articles, 8,9 we found that blood transfusions were followed by an increase in cerebral oxygenation (rSO2C). However, we observed that this increase in oxygen delivery was compensated by a decrease in oxygen blood extraction (FOEC): we speculated that this occurs to keep the oxygen consumption of cerebral tissue constant.…”
Section: Discussionsupporting
confidence: 93%
“…From the Department of Surgical and Medical Critical Care, Section of Neonatology, Careggi University Hospital of Florence, Florence, Italy. spectroscopy (NIRS) in preterm infants has demonstrated that RBC transfusions decrease cerebral blood flow (CBF) velocity [6][7][8] and improve cerebral oxygenation. 8,9 However, the effects of RBC transfusions on the perfusion and oxygenation of other tissues, such as kidneys and gut, have never been investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This then probably counteracts the intended increased oxygen transport to the brain. Volume expansion using red blood cells rather than saline would increase hematocrit, and hence increase cerebral oxygen supply, resulting in a decrease of cFTOE, as previously reported in anemic infants [22,23,24]. …”
Section: Discussionmentioning
confidence: 66%
“…Although there is no clear correlation between haemoglobin concentration and tissue oxygen extraction [62,63], packed-red cell transfusion improves cerebral oxygenation in the anaemic preterm infant [63,64,65]. In addition, a randomised clinical trial has shown that placental-to-foetal transfusion increases rSt O 2 [44], possibly not only due to increased oxygen carrying capacity but also to improved preload.…”
Section: Interventions That Affect Oxygen Delivery To the Brainmentioning
confidence: 99%